2019
DOI: 10.1002/ijc.32195
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in incidence of cervical precancerous lesions in Norway: Nationwide study from 1992 to 2016

Abstract: We analysed patterns in the incidence of cervical intraepithelial neoplasia grades 2 and 3 (CIN2, CIN3) and adenocarcinoma in situ (AIS) by age and histology in 1992–2016 in Norway and described changes in screening tests. Incident cases of CIN2, CIN3, AIS and cervical cancer were identified in the Cancer Registry of Norway, as were all women with at least one screening test. The annual percentage change statistic was used to assess point estimates and changes in age‐specific and age‐standardised incidence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
4
35
0
2
Order By: Relevance
“…However, that being said, this work clearly supports HPV type replacement in vaccinated and unvaccinated women which implies that direct or indirect (herd) effects of the vaccines on the prevalence of HPV types could still be a factor in the recent increase in the incidence of cervical cancer in Sweden and elsewhere. Norway started single cohort vaccination of 12-year-old girls with Gardasil in 2009 achieving a coverage of 89% but, unlike most other nations, did not start catch-up vaccinations until 2016 [81]. It is notable that Norway also observed an increase in the incidence of cervical cancer since vaccination started [82] which is consistent with an increase in the CIN2/3 observed over the same time period [81].…”
Section: 13 X For Peer Review 13 Of 20supporting
confidence: 56%
See 1 more Smart Citation
“…However, that being said, this work clearly supports HPV type replacement in vaccinated and unvaccinated women which implies that direct or indirect (herd) effects of the vaccines on the prevalence of HPV types could still be a factor in the recent increase in the incidence of cervical cancer in Sweden and elsewhere. Norway started single cohort vaccination of 12-year-old girls with Gardasil in 2009 achieving a coverage of 89% but, unlike most other nations, did not start catch-up vaccinations until 2016 [81]. It is notable that Norway also observed an increase in the incidence of cervical cancer since vaccination started [82] which is consistent with an increase in the CIN2/3 observed over the same time period [81].…”
Section: 13 X For Peer Review 13 Of 20supporting
confidence: 56%
“…Norway started single cohort vaccination of 12-year-old girls with Gardasil in 2009 achieving a coverage of 89% but, unlike most other nations, did not start catch-up vaccinations until 2016 [81]. It is notable that Norway also observed an increase in the incidence of cervical cancer since vaccination started [82] which is consistent with an increase in the CIN2/3 observed over the same time period [81].…”
Section: 13 X For Peer Review 13 Of 20supporting
confidence: 56%
“…Note that we used conservative estimates of expected HPV incidence based on survey data from 2004 to 2005, and more recent data suggest that HPV exposure has increased since then, which further strengthens our observation of high vaccine effectiveness. 14 The following limitations of this study are noted. The LTFU study does not have a control arm since participants who received the qHPV vaccine in the base study were offered the 9vHPV vaccination at the end of the base study.…”
Section: Young Women 16-26 Years Of Age (N = 2029)mentioning
confidence: 92%
“…[ 4 ] This method diagnoses 13,000 invasive cancer cases as well as one million precancerous lesions annually. [ 6 ] Although in the health system of Iran, the Pap test is performed on the age group of 20–65 years one to three times a year since 1991 and also it is an effective and nonexpensive test, several studies have indicated that the Iranian women have not greatly welcomed it. [ 7 ] In general, knowledge, attitude, and beliefs are considered the determinant factors for an individual's participation in screening programs.…”
Section: Introductionmentioning
confidence: 99%